2008
DOI: 10.1091/mbc.e08-05-0478
|View full text |Cite
|
Sign up to set email alerts
|

Exon Loss Accounts for Differential Sorting of Na-K-Cl Cotransporters in Polarized Epithelial Cells

Abstract: The renal Na-K-Cl cotransporter (NKCC2) is selectively expressed in the apical membranes of cells of the mammalian kidney, where it is the target of the clinically important loop diuretics. In contrast, the "secretory" NKCC1 cotransporter is localized in the basolateral membranes of many epithelia. To identify the sorting signal(s) that direct trafficking of NKCCs, we generated chimeras between the two isoforms and expressed these constructs in polarized renal epithelial cell lines. This analysis revealed an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 42 publications
1
79
2
Order By: Relevance
“…This variant is also present in mouse, in which both transcripts are expressed in the brain and the longer transcript also in the cochlea (Dixon et al, 1999;Randall et al, 1997), and in human, in which the ratio of the two transcripts varies between expressing tissues (Vibat et al, 2001). In the mammalian gene, the sequence encoded by exon 21 has been proposed to include a conserved basolateral sorting motif that might direct the correct subcellular localisation of the protein in vitro (Carmosino et al, 2008). We are unable to confirm whether this is the case in zebrafish, as we cannot discern which spliceoform is expressed in the ear.…”
Section: Zebrafish Nkcc1 Splice Variants Correspond To Those In the Mmentioning
confidence: 81%
“…This variant is also present in mouse, in which both transcripts are expressed in the brain and the longer transcript also in the cochlea (Dixon et al, 1999;Randall et al, 1997), and in human, in which the ratio of the two transcripts varies between expressing tissues (Vibat et al, 2001). In the mammalian gene, the sequence encoded by exon 21 has been proposed to include a conserved basolateral sorting motif that might direct the correct subcellular localisation of the protein in vitro (Carmosino et al, 2008). We are unable to confirm whether this is the case in zebrafish, as we cannot discern which spliceoform is expressed in the ear.…”
Section: Zebrafish Nkcc1 Splice Variants Correspond To Those In the Mmentioning
confidence: 81%
“…SPAK and oxidative stress response kinase were found to interact with the phosphoacceptor site of NKCC isoforms (7,27,32,34). Apical trafficking and surface expression of NKCC2 have further been established upon application of AVP (13,25,44), and regulatory domains of NKCC2 have been identified (4,47).…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study conducted by Carmosino et al (52) reported that the region corresponding to amino acids 807-884 contains the sorting signal that directs apical trafficking of the NKCC2 protein. The results of the present work showed evidence that this region is not sufficient for NKCC2 exit from the ER.…”
Section: Discussionmentioning
confidence: 99%